2012
DOI: 10.1371/journal.pone.0034194
|View full text |Cite|
|
Sign up to set email alerts
|

The Tumor Suppressive Role of eIF3f and Its Function in Translation Inhibition and rRNA Degradation

Abstract: Deregulated translation plays an important role in human cancer. We previously reported decreased eukaryotic initiation factor 3 subunit f (eIF3f) expression in pancreatic cancer. Whether decreased eIF3f expression can transform normal epithelial cells is not known. In our current study, we found evidence that stable knockdown of eIF3f in normal human pancreatic ductal epithelial cells increased cell size, nuclear pleomorphism, cytokinesis defects, cell proliferation, clonogenicity, apoptotic resistance, migra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 45 publications
4
54
0
Order By: Relevance
“…120 However, eIF3f subunit can ultimately act as a tumor-suppressor-like molecule. 121 Moreover, these data demonstrate that ubiquitous factors of the translational machinery are highly specific for their tumorigenic potential in vivo. It has not been yet demonstrated that changes in eIF3 subunit levels alter the spectrum of the translated mRNAs.…”
Section: The Case For Rapamycin-insensitive Translationmentioning
confidence: 83%
“…120 However, eIF3f subunit can ultimately act as a tumor-suppressor-like molecule. 121 Moreover, these data demonstrate that ubiquitous factors of the translational machinery are highly specific for their tumorigenic potential in vivo. It has not been yet demonstrated that changes in eIF3 subunit levels alter the spectrum of the translated mRNAs.…”
Section: The Case For Rapamycin-insensitive Translationmentioning
confidence: 83%
“…Shi et al also noted that cells with high levels of 3f have reduced amounts of 60S ribosomes relative to 40S ribosomes, apparently caused by 28S rRNA degradation. In contrast, knockdown of 3f expression in stably transfected normal human pancreatic ductal epithelial cells stimulates both cap-dependent and IRES-dependent protein synthesis and cell proliferation, as well as other malignant phenotypes [40,114]. These findings imply that 3f acts to suppress eIF3 activity and protein synthesis, where loss of the subunit would appear to over-activate the initiation factor.…”
Section: Eif3fmentioning
confidence: 90%
“…In a related study, the rabies virus M protein was found to bind to eIF3; this interaction results in inhibition of 5′-cap-dependent translation, but not IRESdependent internal initiation [39]. In contrast, the 3f subunit was shown to inhibit IRES-dependent translation [40]. However, it is not known whether eIF3 interactions with IRESs contribute to malignant transformation following changes in the level of one of its subunits.…”
Section: The Role Of Human Eif3 In Protein Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Although the role of eIF3f in the eIF3 complex has not been defined [11,12,13], shut-off experiments in Schizosaccharomyces pombe showed that over the long term, eIF3f is essential for viability [14]. Studies of translation inhibition indicate that, in mammalian cells, eIF3f is a negative regulator that plays an important role in human cancer [11,15]. We have shown that eIF3f expression is significantly decreased in many human cancers [10,15,16,17].…”
Section: Introductionmentioning
confidence: 99%